Sulla resa degli aggettivi in -TŪRUS e -NDUS: il valdese a confronto con altre varietà di occitano (Carte Romanze, 2023)
Since the Vulgata showed a bulk of future participles and gerundives, its translations in ancient Occitan had to face the problem of how to deal with them. In order to assess the different strategies employed, five vulgarizations of the New Testament have been analyzed. While the most western vulgarization (NTL) often uses verbal adjectives with a -dor ending, with either an active or passive force, its eastern counterparts (NTP, QEO, BVC, NTV) almost categorically refuse this solution, resorting instead to various periphrases. Among the eastern vulgarizations, a particular attention is devoted to the behavior of Waldesian texts (BVC, NTV).
Keywords: Gerundive; Future participle; verbal adjective; vulgarization; Waldensian